KAYA TARI â€œMANUKSMAâ€ SIKAP TANGGAP MEMBACA LINGKUNGAN - Dwi Wahyudiarto (Institut Seni Indonesia Surakarta, 2009)
Chronicle Wanamarta (is] the part of Wanaparwa episode which (is) human being kisah-kasih story with universe. Meruapakan Wanamarta a veiy forest (of] serious condition and is ghostlike, and laterthen.transform to become a big empire as linuwih satriya punjering. Understanding to forest meaning in fact can come near from various dimension. Forest from symbolic meaning dimension, from dimension life (of] universe, from dwelling place side [all] genie, natural ecology dimension, as forest human being dwelling place, as place work, as theft farm, as and asset properties (of] state, andÂ Still many again. How in fact (all] pandawa in face of various the problems, (is] to become the part of gegelisahan which finally have to take choice in forest attitude. Pendawa as excellent orderer, Bima have the spirit (of] remarkable (job/activity], DesignerArjuna offis beauty (of] reliable, Nakula very skilled in farming and developing crop, Observer animal Sadewa and Puntadewa very strong in idea in my me (of] pujabrata in base on spritualÂ workÂ (a II] panda waKeyword: Puppet, Enviroment